Development and Application of a Simple “Easy To Operate” Propidium Monoazide-Crossing Priming Amplification on Detection of Viable and Viable But Non-culturable Cells of O157 Escherichia coli - Zhou, Wenqu; Wang, Kan; Hong, Wei; Bai, Caiying; Chen, Ling; Fu, Xin; Huang, Tengyi; Liu, Junyan (Frontiers in Microbiology, 2020)
O157 Escherichia coli is one of the most important foodborne pathogens causing disease even at low cellular numbers. Thus, the early and accurate of this pathogen is important. However, due to the formation of viable but non-culturable (VBNC) status, the golden standard culturing methodology fails to identify O157 Escherichia coli once it enters VBNC status. Crossing Priming Amplification (CPA) is a novel simple, easy-to-operate detection technology that amplifies DNA with high speed, efficiency, and specificity under isothermal conditions. The objective of this study was to firstly develop and apply a CPA assay with propidium monoazide (PMA) for rapid detection of the foodborne E. coli O157:H7 in Viable but Nonculturable (VBNC) State. Five primers (2a/1s, 2a, 3a, 4s, 5a) were specially designed for recognizing on three targets, which were rfbE, stx1 and stx2, and evaluated for its effectiveness in detecting VBNC cell of E. coli O157:H7 with detection limits of pure VBNC culture at 103 cfu/mL, 105 CFU/mL and 105 CFU/mL for rfbE, stx1 and stx2, respectively, while that of in food samples (frozen pastry and steamed bread) were103 cfu/mL, 105 CFU/mL and 105 cfu/mL. The application of PMA-CPA assay was successfully used on detecting E. coli O157:H7 in VBNC state from food samples. In conclusion, this is the first development of PMA-CPA assay on detection of VBNC cell which was found to be useful and powerful tools for rapid detection of E. coli O157:H7 in VBNC state. Undoubtedly, PMA-CPA method can be of high value to the food industry owing to its various advantages such as speed, specificity, sensitivity and cost-effectiveness.